Driving with Homonymous Visual Field Defects: Driving Performance and Compensatory Gaze Movements - Thomas C. Kübler; Enkelejda Kasneci; Wolfgang Rosenstiel; Kathrin Aehling; Martin Heister; Katja Nagel; Ulrich Schiefer; Elena Papageorgiou (Bern Open Publishing, 2015)
Aim of this pilot study was to assess the driving performance and its relationship to the visual search behavior, i.e., eye and head movements, of patients with homonymous visual field defects (HVFDs) in comparison to healthy-sighted subjects during a simulated driving test. Eight HVFD patients and six healthy-sighted age- and gender-matched control subjects underwent a 40-minute driving test with nine hazardous situations. Eye and head movements were recorded during the drive. Four out of eight patients passed the driving test and showed a driving performance similar to that of the control group. One control group subject failed the test. Patients who passed the test showed an increased number of head and eye movements. Patients who failed the test showed a rightwards-bias in average lane position, probably in an attempt to maximize the safety margin to oncoming traffic. Our study supports the hypothesis that a considerable subgroup of subjects with HVFDs show a safe driving behavior, because they adapt their viewing behavior by increased visual scanning.